2011
DOI: 10.1007/s00122-011-1690-9
|View full text |Cite
|
Sign up to set email alerts
|

QTL for nodal root angle in sorghum (Sorghum bicolor L. Moench) co-locate with QTL for traits associated with drought adaptation

Abstract: Nodal root angle in sorghum influences vertical and horizontal root distribution in the soil profile and is thus relevant to drought adaptation. In this study, we report for the first time on the mapping of four QTL for nodal root angle (qRA) in sorghum, in addition to three QTL for root dry weight, two for shoot dry weight, and three for plant leaf area. Phenotyping was done at the six leaf stage for a mapping population (n = 141) developed by crossing two inbred sorghum lines with contrasting root angle. Nod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
232
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(254 citation statements)
references
References 42 publications
20
232
2
Order By: Relevance
“…We co-located a fresh weight QTL and blade number QTL in the same region on chromosome 8. The co-location of QTLs has been reported in wheat and sorghum, especially for related traits (Mace et al, 2012;Lillemo et al, 2013). We also showed that fresh weight and blade number had a significant correlation.…”
Section: Discussionsupporting
confidence: 74%
“…We co-located a fresh weight QTL and blade number QTL in the same region on chromosome 8. The co-location of QTLs has been reported in wheat and sorghum, especially for related traits (Mace et al, 2012;Lillemo et al, 2013). We also showed that fresh weight and blade number had a significant correlation.…”
Section: Discussionsupporting
confidence: 74%
“…In both wheat ) and sorghum , genetic variation in root system architecture has been reported and associated with increased water capture at depth. In both cases, there is evidence of association with enhanced adaptation to water limitation (Manschadi et al 2007;Mace et al 2011), especially in the case of sorghum, where genomic regions controlling root architecture were associated with yield performance in breeding trials (Mace et al 2011). …”
Section: Water Capture and Use Efficiencymentioning
confidence: 99%
“…A few studies have been conducted to identify the genetic regions controlling specific root traits in barley (Robinson et al, 2016), maize (Zurek et al, 2015;Pestsova et al, 2016), rice (Uga et al, 2011;Liang et al, 2013), sorghum (Mace et al, 2012;Rajkumar et al, 2013), and wheat (Sharma et al, 2011;Hamada et al, 2012;Bai et al, 2013;Christopher et al, 2013;Zhang et al, 2014). In some studies, root traits have been associated with yield and yield components under water-limited environments.…”
Section: Molecular Selectionmentioning
confidence: 99%
“…For instance in rice, a QTL for deep rooting DEEP ROOTING 1 (DRO1) was identified (Uga et al, 2011) and recently cloned in a shallow-rooting rice cultivar to enhance its yield under drought conditions by increasing deep rooting (Uga et al, 2013). In sorghum, genetic association between narrower nodal root angle and increased grain yield has been found, and manipulating nodal root angle through molecular breeding has been proposed to improve drought adaptation (Mace et al, 2012). In maize, QTL for the root traits primary root length, primary root diameter, primary root weight, and weight of the adventitious seminal roots and some of these QTL are overlapping with QTL for grain yield in the field (Tuberosa et al, 2002b).…”
Section: Molecular Selectionmentioning
confidence: 99%
See 1 more Smart Citation